Metaphorical enhancements of the us/them asymmetry in war speeches of American presidents in the years 1917–1972 - Barbara Chmielewska (Currents)
This paper aims to analyse the metaphorical conceptualizations that highlight the dichotomy between the countries and people in the service of political agendas. The study introduces the brief account of Lakoff’s and Sandikcioglu’s remarks on the use of figurative language in a political discourse. This is followed by a systematic analysis of the metaphorical conceptualizations that emphasize the Us/Them asymmetry in the speeches of American presidents regarding World War I, World War II, and the Vietnam War.